Analisis Penerapan Sistem Informasi Akuntansi dengan Memenuhi Akuntabilitas Pengelolaan Laporan Keuangan: (Studi Kasus Yayasan Smk Kesehatan Delima Nusantara Medan) - Maharani Zaida; Yenni Samri Juliati Nasution; Nurwani Nurwani (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This study aims to determine the application of accounting information systems for cash receipt procedures and cash disbursement procedures by fulfilling the accountability of financial statement management (case study of the SMKS Delima Nusantara Foundation Medan). This research uses a descriptive qualitative approach. The research subjects amounted to three people, including financial administration staff, treasury staff, and nursing principals. Data collection techniques in this study are interview techniques, observation and documentation. Based on the results of the study, it is found that the application of the accounting information system in the SMKS Delima Nusantara Foundation Medan, especially in the cash receipts and disbursements procedure, has been said to be effective and in accordance with the applicable accounting information system procedures. However, in terms of accountability of the financial statements of the SMKS Delima Nusantara Foundation Medan according to the principle of accountability is still less effective due to lack of awareness in preparing the accountability report every month.